Diversity of threatened medicinal plants of Indian Himalayan Region. (2nd November 2021) - Mehta, Poonam; Bisht, Kapil; Sekar, K. Chandra
Abstract: Medicinal and aromatic plants (MAPs) are frequently being used for various ailments since time immemorial by a vast range of human communities. The Indian Himalayan Region (IHR), which forms part of one of the 36 global biodiversity hotspots, is known for its rich and unique biodiversity elements. In last decades, plant-based medicines have gained popularity over synthetic pharmaceutical products as they are retained less harmful. However, increased demand of these plant-based medicinal products has caused over-harvesting, unmonitored trade, habitat destruction and anthropogenic pressure on MAPs. In view of their importance, the present study aims to document the diversity of threatened plants in IHR that are medicinally important, their distribution in 12 Himalayan states and suggest conservation measures. A total of 112 plant species were documented of which 19 species were found to be in high-risk categories viz. critically endangered (seven), endangered (seven) and vulnerable (five) as per IUCN. Distribution, life-forms, medicinal values, plant parts used, threat categories, population trends, market value and conservation approaches of the species are also presented. The study strongly recommends prohibition of unmanaged extraction of medicinally important threatened plants from the wild and encourages their cultivation.